Control and hysteresis reduction in prestressed curved unimorph actuators using model predictive control. (February 2014) - Kim, Byeongil; Washington, Gregory N; Yoon, Hwan-Sik
Curved piezoceramic unimorph actuators exhibit strong nonlinearities due to their special architecture that enables large motion amplification. Among these nonlinearities, hysteresis is the most problematic as it makes it difficult to predict the displacement of the actuator for a given input voltage. Therefore, it has been difficult to use these actuators in precision displacement control applications. In order to overcome this difficulty, this research is focused on the development of an effective reference-tracking displacement control algorithm for such actuators. For this purpose, two linear (proportional–integral and internal model) and two nonlinear (sliding mode and model predictive sliding mode) controllers are designed and implemented. These controllers are applied to the curved piezoceramic unimorph actuator to control the displacement of the actuator for multiple sinusoidal voltage inputs at various frequencies. Experimental results are obtained, and their performance is compared both qualitatively and quantitatively. As a part of the model-based controller design, a new actuator model is also developed based on the mechanical second-order equation with an additional phase lag term to describe the hysteretic effect.